Front Cover: Array Microcell Method (AMCM) for Serial Electroanalysis (ChemElectroChem 5/2020). Issue 5 (6th February 2020) - Alden, Sasha E.; Siepser, Natasha P.; Patterson, Jacqueline A.; Jagdale, Gargi S.; Choi, Myunghoon; Baker, Lane A.
Abstract : The Front Cover illustrates a method that is described to address electrode arrays through a movable micropipette to contact the electrode array. In this case, the electrodes are lithographically defined to look like Texas longhorns! More information can be found in the Article by S. E. Alden et al. on page 1084 in Issue 5, 2020 (DOI: 10.1002/celc.201901976 ).